The Relationship between Self-Control and Academic Cheating in Students of SMA Negeri 5 Surakarta - Hertindha, Rindhi Rezqi; Astuti, Budi; Santoso, Taufik Sani (Universitas Ahmad Dahlan, 2022)
This correlational study aimed to find out the relationship between self-control and academic dishonesty among students in SMA Negeri 5 Surakarta Data were collected from 222 randomly selected 11th-grade students using self-control and academic dishonesty scales. The product Moment Correlation analysis result showed a correlation coefficient of -0.188, indicating a negative correlation between self-control and academic dishonesty. In other words, students with better self-control tend not to commit academic dishonesty. This study result serves as a reference for school counselors in developing services to improve students’ self-control.